PENYULUHAN KOMUNIKASI PERSUASIF UNTUK MENINGKATKAN PENGETAHUAN DAN SIKAP MASYARAKAT DALAM PENANGGULANGAN GANGGUAN AKIBAT KEKURANGAN YODIUM - , ASIH SETYANI; , DR. Toto Sudargo, SKM, M.Kes. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background: One of the strategies of health promotion in the context of Iodine Deficiency Disorders (IDD) prevention is health education using persuasive communication. Objective: To measure the effect of persuasive communication methods toward changes in knowledge and attitudes of childbearing age women in the prevention of IDD in Kepil district, Wonosobo regency. Methods: This was a quasi-experimental study with non equivalent with pre-test and post-test of control group design. Subject of the study were women of childbearing age in Pulosaren village. There were as many as 68 respondents who were interviewed using questionnaire. The data then were analyzed using ttest for normally distributed data and using Mann-Whitney, Wilcoxon for skewed distributed data. Results: The results of analysis (pre-test to post-test 1) showed that health education using persuasive communication produces a mean difference of knowledge 5,56, and the mean difference in attitude 4,68. Non persuasive communication method produces a mean difference of knowledge 3,74 and the mean difference in the attitude 1,35. Results of analysis (pre-test to post-test 2), showed that health education using persuasive communication produces a mean difference of knowledge 6,00 and attitudes 5,65. Non persuasive communication method produces a mean difference of knowledge 3,21 and the mean difference of attitude 2,03 Conclusion: The method of persuasive communication can improve respondents' awareness of IDD. Persuasive communication methods can improve respondents' attitudes about IDD. Persuasive communication methods more effectively improves the knowledge and attitudes of respondents about IDD than counseling without persuasive communication.